Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Kesehatan oleh Peserta JKN-KIS di wilayah kerja Puskesmas Kondodewata Kabupaten Tana Toraja - Arruan, Agustina (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2025)
The utilization of health services by JKN-KIS participants at Kondodewata Health Center remains below the expected visit target. This is influenced by factors such as accessibility, available facilities, low public knowledge, and the availability of health workers when the community needs services. This study aims to determine the factors associated with the utilization of health services by JKN-KIS participants in the working area of Kondodewata Health Center, Tana Toraja Regency. This research is quantitative in nature, using a cross-sectional approach. The population consisted of all JKN-KIS participants, both PBI (Contribution Assistance Recipients) and Non-PBI, totaling 5,641 people. A sample of 76 respondents was selected using simple random sampling. The instrument used was a questionnaire. Data analysis was conducted using univariate and bivariate analysis with the Chi-square test at a significance level of p-value = 0.05. The results of the study showed a significant relationship between JKN knowledge and the utilization of health services (p-value = 0.041). There was a significant relationship between accessibility and health service utilization (p-value = 0.000). There was also a significant relationship between the availability of health workers and health service utilization (p-value = 0.012). A significant relationship was also found between available facilities and health service utilization (p-value = 0.000). The study concludes that there is a relationship between knowledge, accessibility, availability of health workers, and facilities with the utilization of health services. It is recommended to improve public knowledge, ensure equitable distribution of health workers, and enhance access to health service locations so that communities can more easily obtain services.